Edukasi Penanganan Dan Pengolahan Daging Kurban Di Masjid Al Ikhsan Kramat Selatan, Kota Magelang, Jawa Tengah - Gunawan (indoensia), Muhammad Iqbal Fanani; Putri (indonesia), Soraya Kusuma; Nugraheni (indoensia), Martha Arum; Wulan (indonesia), Rahayu; Pramono (indoensia), Pradipta Bayuaji (JURNAL KASTARA, 2023)
Holiday celebrations carried out by Muslims include Eid al-Fitr, and the second is Eid al-Adha, or what people call the Eid al-Sacrifice holiday. Eid al-Adha has provisions that have been determined according to Islamic law. These provisions include being Muslim, financially capable, resourceful, and mature. People who are said to have abilities are people who are sufficient in terms of assets, both for themselves and their families. Sacrificial meat is a food product that has the potential for danger both biologically, physically, and chemically, which occurs when the sacrificial animal is slaughtered. Therefore, it is necessary to implement cleanliness and sanitation during the process of handling and processing sacrificial meat for the sacrificial animal slaughter committee at the Al-Ikhsan Mosque and the Sanden community in South Kramat, Magelang City.